2016
DOI: 10.1101/058347
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exploring the genetic architecture of inflammatory bowel disease by whole genome sequencing identifies association atADCY7

Abstract: To further resolve the genetic architecture of the inflammatory bowel diseases, ulcerative colitis and Crohn's disease, we sequenced the whole genomes of 4,280 patients at low coverage, and compared them to 3,652 previously sequenced population controls across 73.5 million variants. We then imputed from these sequences into new and existing GWAS cohorts, and tested for association at ~12 million variants in a total of 16,432 cases and 18,843 controls. We discovered a 0.6% frequency missense variant in ADCY7 th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 42 publications
2
35
0
Order By: Relevance
“…Genome‐wide association studies (GWAS) have now identified 235 inflammatory bowel disease (IBD)‐associated susceptibility loci, substantially expanding our understanding of the biology underlying these diseases . Early genetic studies focused on searching protein coding sequences, although it is now recognised that coding variation explains only ~20% of genetic variation associated with IBD GWAS loci .…”
Section: Introductionmentioning
confidence: 99%
“…Genome‐wide association studies (GWAS) have now identified 235 inflammatory bowel disease (IBD)‐associated susceptibility loci, substantially expanding our understanding of the biology underlying these diseases . Early genetic studies focused on searching protein coding sequences, although it is now recognised that coding variation explains only ~20% of genetic variation associated with IBD GWAS loci .…”
Section: Introductionmentioning
confidence: 99%
“…Fourth, it has been proposed that rare variants – which are not included on GWAS chips but which could have much larger effect sizes – might account for some of the missing heritability. However, several studies have now been performed to attempt to identify rare disease‐associated variants, but without much success – mirroring the situation in other diseases . Fifth, because most GWAS SNPs are proxies for the true causal variant, estimates of variance based on these are likely to underestimate the true attributable risk at each locus.…”
Section: More Work To Domentioning
confidence: 99%
“…Moreover, there is increasing evidence that genome sequencing might be more powerful at detecting exonic variants than whole exome sequencing . An example of applying low coverage exome sequencing to find an associative gene is the identification of ADC7Y in a study of 4280 patients at low coverage.…”
Section: Wes Panels and Wgsmentioning
confidence: 99%